2012
DOI: 10.1371/journal.pone.0037124
|View full text |Cite
|
Sign up to set email alerts
|

Irradiated Male Tsetse from a 40-Year-Old Colony Are Still Competitive in a Riparian Forest in Burkina Faso

Abstract: BackgroundTsetse flies are the cyclical vectors of African trypanosomosis that constitute a major constraint to development in Africa. Their control is an important component of the integrated management of these diseases, and among the techniques available, the sterile insect technique (SIT) is the sole that is efficient at low densities.The government of Burkina Faso has embarked on a tsetse eradication programme in the framework of the PATTEC, where SIT is an important component. The project plans to use fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…p . gambiensis [36]. It was showed that a dose of 120 Gy did not affect mating competitiveness of G .…”
Section: Introductionmentioning
confidence: 99%
“…p . gambiensis [36]. It was showed that a dose of 120 Gy did not affect mating competitiveness of G .…”
Section: Introductionmentioning
confidence: 99%
“…The Government of Senegal opted to procure the sterile flies from the Centre International de RechercheDéveloppement sur l′Élevage en zone Subhumide (CIR-DES) in Burkina Faso, where a colony of the target species has been maintained for the last 40 years [23] rather than establishing and operating a costly national rearing facility to produce the sterile male flies. This decision required the development of transport and handling protocols to retain the female flies in CIRDES for their colony and transport of the male flies as irradiated pupae.…”
Section: Introductionmentioning
confidence: 99%
“…Aerial release is recommended to ensure homogeneous distribution of the released insects (Mubarqui et al 2014). It is thereafter critical to assess the competitiveness, survival and dispersal of the released males in the environmental conditions of the target area in order to make sure that they will be able to compete with their wild counterparts (Bellini et al 2013;Sow et al 2012). Finally, the released insects will have to show a similar behaviour as their wild counterparts ).…”
Section: Pests and Vector-borne Diseases In The Livestock Industry 437mentioning
confidence: 99%